"Please give me an invoice": VAT evasion and the Portuguese tax lottery. Issue 5 (10th June 2019) - Wilks, Daniela C.; Cruz, José; Sousa, Pedro
Abstract : Purpose: The Portuguese tax authority implemented a lottery to encourage citizens to request invoices as a strategy to fight value-added tax (VAT) evasion. As the law does not require citizens to request sales invoices with the consumers' tax number, doing so is a form of voluntary cooperation in tracking down tax evaders. The purpose of this paper is to understand why ordinary citizens decide to join forces with tax authorities in the fight against VAT evasion by requesting invoices with their tax identification number. Design/methodology/approach: An empirical study was conducted to explore the underlying motivation for Portuguese consumers to request sales invoices with their personal tax identification. The study combines quantitative and qualitative data. Findings: The results from this study show that rewarding citizens is clearly a factor to be considered in any policy to maximize citizens' cooperation in tracking down tax evaders. They indicate that fiscal benefits have a stronger effect on the request of invoices than the lottery and that it is necessary to promote good governance and justice. Practical implications: Findings should be used to inform a cost-effective public policy that takes into account citizens' concerns and combine deterrent measures and rewards in the form of tax benefits, rather than tax lotteries. Originality/value: This paper provides new insights into VAT lotteries, which seem to be increasingly favored by policy makers but are an area under-researched. By recommending a course of action to maximize citizens' cooperation in tracking down tax evaders, the paper provides useful practical implications and is a contribution for the study of VAT evasion policies.